2011
DOI: 10.2478/v10187-011-0043-x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Knot Net for Calculation of Quadratic Triangular B-spline Surface of Human Head

Abstract: This paper deals with calculation of the quadratic triangular B-spline surface of the human head for the purpose of its modeling in the standard videocodec MPEG-4 SNHC. In connection with this we propose an algorithm of generation of the knot net and present the results of its application for triangulation of the 3D polygonal model Candide. Then for the model and generated knot net as well as an established distribution of control points we show the results of the calculated quadratic triangular B-spline surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…From the above analysis, it can be found that the location of the knots in the parametric domain play an important role in determining the DMS-splines. A major restriction on the position of the knot-cloud is that three knots can not be collinear [57] for a smooth surface. This is a severe task to obtain the knot-cloud over the parametric domain.…”
Section: Description Of the Dms-splinesmentioning
confidence: 99%
See 2 more Smart Citations
“…From the above analysis, it can be found that the location of the knots in the parametric domain play an important role in determining the DMS-splines. A major restriction on the position of the knot-cloud is that three knots can not be collinear [57] for a smooth surface. This is a severe task to obtain the knot-cloud over the parametric domain.…”
Section: Description Of the Dms-splinesmentioning
confidence: 99%
“…This is a severe task to obtain the knot-cloud over the parametric domain. In this study, the algorithm for generating the knot-net proposed by Mihalík [57] is adopted. This method considers the distance between the main knot and the extra knot as the only variable.…”
Section: Description Of the Dms-splinesmentioning
confidence: 99%
See 1 more Smart Citation